Prototype Pengembangan Buku Ajar Berbasis Mobile Learning pada Materi Menerapkan Pengelolaan Informasi Melalui Web Log (Blog) Kelas X OTKP SMK PGRI 13 Surabaya - Rizal Amirul Iba'd; Triesninda Pahlevi (Universitas Negeri Surabaya, 2020)
The learning process requires teaching materials that can support learning in the classroom, be it modules or interactive teaching materials. Interactive teaching materials can use gadgets as a medium to support the learning process. Based on observations at SMK PGRI 13 Surabaya, the teacher only has a book handle and teaches with brwosing. This makes students passive in learning activities and can bring up lessons about the sophistication of various gadgets. Textbook base mobile learning are an effort to optimize the use of student smartphones so students become more independent and do not miss lessons. In this study using the ADDIE development model which has 5 stages, namely analysis; design; development; implementation; evaluation. The purpose of this study was to determine the development, and feasibility textbook base mobile learning. Based on the validation assessment, obtained 89.5% material validation experts which is the average of the number of validation assessments from the Office Administration Education Lecturer, Surabaya State University, and Surabaya PGRI 13 SMK teachers and 91.6% media validation from Curriculum and Education Technology Lecturers, Surabaya State University. This shows the media developed by researchers is categori as very feasible and can use in learning process.